A pH sensitive, loop-mediated isothermal amplification assay for detection of Salmonella in food - Charoenpanich, Pornsri; Mungkung, Anussara; Seeviset, Nattakan (Science, Engineering and Health Studies, 2020)
Salmonella is a common foodborne pathogen. This study aimed to develop a rapid detection method for Salmonella spp. in food by using a pH sensitive, loop-mediated isothermal amplification (LAMP) assay. Firstly, a suitable pH indicator was selected to follow the change in pH of LAMP reactions. Then, the best primer set was selected from among three previously approved primer sets specific to the genes invA, invE, and phoP. The amplification-positive reactions were easily detectable with neutral red at a concentration of 15 mM (color change from faint orange to red). The best primers were those specific to phoP when incubated at 63.5°C for 1.5 h. The developed assay was validated for detection of Salmonella Typhimurium in spiked minced chicken meat and liquid egg with a sensitivity of 2 CFU/g or 2 CFU/mL. With this novel, pH-sensitive LAMP assay, Salmonella can be detected in food in 6 h.